Serum Lipase Amylase Ratio in Predicting Aetiology, Severity and Outcome of Acute Pancreatitis in a Tertiary Care Hospital (Bangladesh Critical Care Journal, 2017)
Background: Acute pancreatitis is a relatively common disease with variable prevalence in different countries. Different modalities are available for predicting aetiology, severity and outcome of acute pancreatitis with different sensitivity and specificity. Moreover, some are not widely available, some are very expensive. A single, cheap, widely available marker with high sensitivity and specificity is yet to be identified. The present study intends to find out the utility of serum lipase amylase ratio in predicting the aetiology, severity and outcome of acute pancreatitis.Methods: This prospective, observational study was done at the Department of Gastrointestinal Hepatobiliary & Pancreatic Disorders (GHPD), BIRDEM General Hospital, Dhaka, during the period of July 2014 to March 2016. A total of 71 patients with acute pancreatitis were included. Complete blood count, serum amylase, serum lipase, serum calcium, liver function test, renal function test, fasting lipid profile, ultrasonography of whole abdomen, CT scan of upper abdomen and arterial blood gas (ABG) were done in all patients. Statistical analysis was done with SPSS version 16.Results: Among 71 patients, 23(32.4%) were due to biliary cause, 15(21.1%) were due to hypertriglyceridaemia, 4(5.6%) were due to alcohol and 22(31%) were due to unknown causes. 45 (63.4%) patients had mild attack, 10(14.1%) patients had moderate attack and 16(22.5%) patients had severe attack of acute pancreatitis. Out of 71 patients, 17(23.9%) developed complication whereas 54(76.1%) developed no complication. Serum lipase amylase ratio in patients with biliary pancreatitis was 1.40±0.39 and in patients with non-biliary pancreatitis was 2.39±0.84(p